Академічна філософія як «нове просвітництво» для діалогічної цивілізації - Єрмоленко, А.М. (Вісник НАН України, 2019)
Предметом статті є аналіз провідних тенденцій розвитку філософії в
Інституті філософії імені Г.С. Сковороди НАН України в контексті парадигмальних змін у світовій філософії та формування діалогічної цивілізації. Висвітлено здобутки науковців Інституту, дослідження яких ще за
радянських часів виходили за межі марксистської парадигми, закладаючи
підвалини для розвитку філософії в пострадянський період. Показано, що
філософія незалежної України і мовно, і концептуально розвивається в річищі світової філософської думки, розбудовуючи концепції демократичної держави та громадянського суспільства і реагуючи на виклики сучасної
доби, пов'язані з ситуацією «постправди», моральним релятивізмом та нігілізмом. In this article, written upon the occasion of the 100th anniversary of National Academy of Sciences of Ukraine, the author
analyzes key trends of development of philosophy in the H.S. Skovoroda Institute of Philosophy of NAS of Ukraine.
This analysis is put into the broader context of the paradigmatic changes of the world philosophy in the past decades.
A major focus is put on achievements of the Institute’s research fellows in the past decades. Despite domination of the
Marxist-Leninist ideology in the Soviet period, the Institute’s researchers went beyond the limits of the Marxist paradigm,
and laid the foundation for development of philosophy during the post-Soviet period. In the independent Ukraine,
philosophy is developing, both with regard to its language and methodology, in line with global philosophical trends, in
the fields like philosophic anthropology, social philosophy, ethics, practical and political philosophy, logic, methodology
of science, environmental philosophy etc. Contemporary philosophy in Ukraine took great efforts to develop concepts of
democratic state and civil society. It reacts to today’s challenges, related to «post-truth» and «hybrid worldviews», trying
to counteract dangers of moral relativism and nihilism with regard to norms and values. The author stresses that
truth and ethos of research community are the important imperative requirements for the further development of philosophy
in Ukraine.